A socio-ecological model of the management of leprosy reactions in Indonesia and India using the experiences of affected individuals, family members and healthcare providers - Annisa Ika Putri; Ruth M. H. Peters; Kevin De Sabbata; Brittney S. Mengistu; Regitta I. Agusni; Medhi Denisa Alinda; Joydeepa Darlong; M. Yulianto Listiawan; Cita R. S. Prakoeswa; Stephen L. Walker; Marjolein B. M. Zweekhorst (BMC Health Services Research)
Abstract Background Leprosy reactions (LR) are immune-mediated complications of leprosy that may be associated with severe and irreversible nerve damage. Non-medical aspects, such as financing, service provision, and healthcare resources in the management of LR are generally overlooked as studies tend to concentrate on clinical features and treatment. Barriers to accessing care and services are a major cause of suboptimal care for people with leprosy. This study aims to explore the barriers to and facilitators of high-quality care and management of LR in two leprosy-endemic countries with different health care models – Indonesia and India – and identify areas for improvement. Methods A socio-ecological model was adopted. Data were obtained from 66 interviews with individuals who experienced LR and were seeking care at the two study sites. In addition, immediate family members of individuals with LR and healthcare workers attending to people with leprosy participated in seven focus group discussions (FGDs). Results This study highlights the significant impact of public health insurance regulations and uptake at the macrosystem level on the provision of healthcare services, clinical decision-making, care expenditure, and the psychological well-being of individuals with LR in Indonesia and India. Lack of specialized health professionals and communication challenges were identified in both study populations. Indonesian participants encounter additional challenges due to a fragmented information system and drug shortages. This study identifies key facilitators in providing high-quality care for LR-affected individuals, including financial assistance, availability of corticosteroid alternatives, timely provision of care, and counselling. It found that the high coverage of public health insurance cards in the Indonesian model has increased access to care among individuals affected by LR, despite the challenges. Conversely, the Indian model of care offers treatment subsidies. The advantage of the Indonesian model is its ability to provide wider access to high-quality care, whereas the Indian model focuses on those in most need. This study emphasizes the importance of addressing these challenges through improved communication strategies, education aimed at the affected individuals, and accessible medical care. Furthermore, variations in care-seeking behaviour and self-care practices were observed in both sites, underscoring the need for culturally sensitive and comprehensive approaches to the management of LR. Conclusion The study findings demonstrate that the factors identified at the four systemic levels are interrelated and have an impact on the access, acceptability, and management of LR services. Despite its accessibility and wider coverage of public health insurance, the integrated service model in Indonesia faces challenges associated with complex regulations and the availability of medication. India’s care model offers intensive, specialised care but has difficulties in ensuring sufficient health personnel, resources, and public health insurance coverage. These findings highlight the need to address these challenges to ensure timely, effective, and comprehensive care for individuals with LR.